2014
DOI: 10.3201/eid2004.131328
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Surveillance in Urban and Rural Areas of Niger, April 2010–March 2012

Abstract: Knowledge of rotavirus epidemiology is necessary to make informed decisions about vaccine introduction and to evaluate vaccine impact. During April 2010–March 2012, rotavirus surveillance was conducted among 9,745 children <5 years of age in 14 hospitals/health centers in Niger, where rotavirus vaccine has not been introduced. Study participants had acute watery diarrhea and moderate to severe dehydration, and 20% of the children were enrolled in a nutrition program. Of the 9,745 children, 30.6% were rotavirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 25 publications
4
24
0
2
Order By: Relevance
“…In this study, RVA genotype G12P[8] was the prevalent genotype, corroborating previous reports conducted in Asian, European, American, and African continents, demonstrating the epidemiological relevance of this genotype worldwide [Cunliffe et al, ; Page et al, ; Potgieter et al, ; Jere et al, ; Page et al, ; Seheri et al, ; Bucardo et al, ; Luchs et al, ]. The high proportion of genotype G12 in African populations is believed to be associated with the emergence of genotype P[6] [Steele and Ivanoff, ; Page et al, ; Seheri et al, ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, RVA genotype G12P[8] was the prevalent genotype, corroborating previous reports conducted in Asian, European, American, and African continents, demonstrating the epidemiological relevance of this genotype worldwide [Cunliffe et al, ; Page et al, ; Potgieter et al, ; Jere et al, ; Page et al, ; Seheri et al, ; Bucardo et al, ; Luchs et al, ]. The high proportion of genotype G12 in African populations is believed to be associated with the emergence of genotype P[6] [Steele and Ivanoff, ; Page et al, ; Seheri et al, ].…”
Section: Discussionsupporting
confidence: 88%
“…The preliminary data from these countries showed that RVA vaccines were safe and effective in protecting children from severe diarrhea caused by RVA. However, the impact of regionally prevalent and mixed genotypes on vaccine effectiveness in Africa is not yet clear, and needs to be monitored [Madhi et al, ; Cunliffe et al, ; Groome et al, ; Page et al, ; Bar‐Zeev et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…G12 RVA are considered emerging human RVA strains, and the lineage III G12 allele has spread worldwide rapidly [18, 19]. Strain G12P[8] was associated with a large outbreak of pediatric gastroenteritis in Rochester in 2007 (an outbreak detected through the NSVN) [13], and this genotype has been reported recently in Niger [20], Spain [21], Nicaragua [22], Haiti [23], and Australia [24]. It appears that G12P[8] strains now are established in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in our study, G2P [4] proved to be the second-most prevalent genotype circulating in the south of the country where the study was conducted. However, in Niger and the Democratic Republic of Congo, G2P [4] was the predominant genotype before vaccine introduction [24,25]. However, G2P [4] was found circulating in the Central Africa Republic at a rate of 13%, in Cameroon at 5.9%, Burkina Faso at <1% and Gabon at <2% [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%